Transformation of University Colleges to Full-Pledged Universities: A Proposed Conceptual Framework for Malaysian Higher Learning Institutions - Sara Asmawati, Shariffuddin; Jamal Rizal, Razali (IASE, 2017)
Transformation of higher education is inevitable and is persistently occurring around the globe. One of the prominent outcomes is the changes of higher education institutions. In Malaysia, among the major changes observed is the conversion of college universities to full-pledged universities. Therefore, this study reviews the requirements involved in transforming university colleges to universities, the key strategies implemented and the impacts it has on the academics. Three impacts of the transformation on the academics are identified namely the impacts on their identity, career and academic activities. Finally, this paper proposes a conceptual framework in investigating the issues and challenges related to transforming Malaysian’s university colleges to full-pledged universities.